Lowest theme vowels or highest roots? An ‘unaccusative’ theme-vowel class in Slovenian - Simonović, Marko; Mišmaš, Petra (Glossa (London), 2022)
This paper focuses on the e/i theme vowel class of verbs in Slovenian to bring together two seemingly unrelated debates: (i) the debate on the correlation between theme vowel classes with certain argument structures and (ii) the debate on the status of derivational affixes within the framework of Distributed Morphology. Our core data come from a list of 108 unaccusative verbs obtained using the adjectival active l-participles as an unaccusativity diagnostic. We show that (i) no unaccusative verbs belong to the two largest theme vowel classes in Slovenian (a/a and i/i), whereas (ii) the two big theme vowel classes tend to get accusative arguments quite frequently. Most importantly, (iii) the e/i-class stands out since more than one half of the unaccusative sample falls into it. The e/i-class is furthermore exceptional in that its theme vowel surfaces in adjectival l-participles, it is the theme vowel class to which inchoatives in inchoative-causative pairs belong and it behaves uniformly with respect to stress. Based on this behavior which sets the e/i-class apart from other theme vowel-classes, we argue that the morpheme e/i is better analyzed as a derivational affix. We further argue, following Lowenstamm (2014), that derivational affixes are transitive roots rather than categorizers and propose detailed PF and LF instructions for the root under consideration.